2020
DOI: 10.1016/j.jjcc.2019.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Low ankle brachial index predicts poor outcomes including target lesion revascularization during the long-term follow up after drug-eluting stent implantation for coronary artery disease

Abstract: Background: Peripheral arterial disease (PAD) frequently coexists with coronary artery disease (CAD). The ankle-brachial index (ABI) is widely used for the screening for PAD. Low ABI is associated with short-term clinical outcomes in patients receiving coronary drug-eluting stent (DES) implantation. However, there is no report to examine the relationship between lower ABI and long-term clinical outcomes after DES implantation. Thus, we investigated the clinical long-term impact of low ABI after DES implantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 26 publications
1
17
0
1
Order By: Relevance
“…After applying our predefined inclusion and exclusion criteria, 49 studies were further removed for various reasons. Thus, 9 studies 9,11 17,22 were finally included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After applying our predefined inclusion and exclusion criteria, 49 studies were further removed for various reasons. Thus, 9 studies 9,11 17,22 were finally included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies 9,11 14,17,22 reported the MACE as an outcome measure. As shown in Figure 2, a fixed-effect model was selected because there was no significant between-study heterogeneity ( I 2 = 27.2%, P = .212).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ankle brachial index (ABI) has been reported as an indicator of clinical outcomes in patients who underwent PCI (8)(9)(10). ABI is widely performed in patients with TAA/ AAA, as TAA/AAA is often complicated with peripheral artery disease (11).…”
Section: Introductionmentioning
confidence: 99%